2012
DOI: 10.3858/emm.2012.44.8.055
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of cancer cell migration regulated by Gβγ and phosphatidylinositol 3-kinase

Abstract: Phosphatidylinositol 3-kinase (PI3K) is essential for both G protein-coupled receptor (GPCR)- and receptor tyrosine kinase (RTK)-mediated cancer cell migration. Here, we have shown that maximum migration is achieved by full activation of phosphatidylinositol 3,4,5-trisphosphate-dependent Rac exchanger 1 (P-Rex1) in the presence of Gβγ and PI3K signaling pathways. Lysophosphatidic acid (LPA)-induced migration was higher than that of epidermal growth factor (EGF)-induced migration; however, LPA-induced activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…is possible that G protein-coupled LPA receptor evokes activation of PI3K and release of Gβγ subunit and leads to the activation of P-Rex1. In line with this, it has been reported that LPA induces cancer cell migration through the activation of P-Rex1 [15].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…is possible that G protein-coupled LPA receptor evokes activation of PI3K and release of Gβγ subunit and leads to the activation of P-Rex1. In line with this, it has been reported that LPA induces cancer cell migration through the activation of P-Rex1 [15].…”
Section: Discussionsupporting
confidence: 57%
“…Plethora of reports suggests that LPA mainly activates three MAPK signaling pathways including the Ras/MEKK/ MAPK, p38 MAPK, and JNK pathways [2,21]. In addition to these MAPK signaling pathways, it also has been reported that LPA stimulates PI3K signaling pathways and regulates variety of physiological responses such as DNA synthesis and cell motility [15,17]. Although the mechanism underlying activation of PI3K is still unclear, inhibition of PI3K…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell migration and invasion play a critical role in cancer cell progression and subsequent cancer metastasis (Kirui et al, 2010). The role of Gbg signaling in cell migration and invasion is thoroughly investigated and well documented (Kirui et al, 2010;Tang et al, 2011;Kim et al, 2012;Vázquez-Prado et al, 2016). In addition to PI3K, Gbg signaling contributes to full activation of PIP3-dependent Rac exchanger 1 (P-Rex1) and thus to Rac1-mediated cell mobility (Dbouk et al, 2012;Kim et al, 2012).…”
Section: Inhibition Of Gbg Signaling By Statinsmentioning
confidence: 99%
“…Thus, small molecules that can inhibit enzymes responsible for cell migration represent an intriguing new direction for cancer chemotherapy. Phosphatidylinositol 3,4,5-trisphosphate (PIP 3 )-dependent Rac exchanger (P-Rex) 1 and P-Rex2 are increasingly recognized for their role in the metastasis of breast cancer, prostate cancer, and melanoma (Berger et al, 2012; Lindsay et al, 2011; Qin et al, 2009; Sosa et al, 2010), and it has been shown that P-Rex enzymes can drive migratory and invasive phenotypes in laboratory cell lines (Campbell et al, 2013; Kim et al, 2012). Therefore, P-Rex1 and P-Rex2 represent attractive therapeutic targets in cancers where P-Rex overexpression is responsible for clinical progression.…”
Section: Introductionmentioning
confidence: 99%